Etnomatematika Permainan Kelereng Sebagai Teknik Belajar Matematika Sekolah Dasar - Silfiana, Nita; Widyastuti, Wahyuning (Indonesian Journal of Islamic Elementary Education, 2021)
Ethnomathematics is a culture in which there are mathematical concepts. The existenceof this culture has a very big influence on learning mathematics. The purpose of this research is to find out and explain the mathematical elements contained in the marbles game and their use in the context of learning mathematics. This research uses literature study. The result of this study is to find out that in the marbles game there is a mathematical ethnicity associated with geometric concepts, for example the concepts of circles, balls, triangles and distances. The concepts contained in the marbles game are used to introduce and provide an understanding of the concepts of geometry and distance through local cultural games.